Beginner researcher training for Giovanni high school students in Kupang, East Nusa Tenggara - Maria Yulita Nara; Maria A.N Letuna; Felisianus Efrem Jelahut (Universitas Muhammadiyah Malang, 2023)
The purpose of the Beginner Researcher Training activities for Giovanni Kupang Senior High School students is to help students become competent researchers in order to participate in scientific activities and be able to compete academically in scientific competitions such as the Olimpiade Sains Nasional (OPSI). This goal also supports the realization of a literacy awareness movement that has been programmed and implemented well by Giovanni Kupang's Senior High School partners. Beginner researcher training activities were held at Giovanni Senior High School in Kupang City, East Nusa Tenggara Province. Implementation of training activities for novice researchers is carried out using training and mentoring methods which are carried out through Material Presentations/Providing Information, Questions and Answers and Discussions, Focused Group Discussions (FGD) and Technical Guidance. Based on the implementation of community service activities and evaluation with partners, it can be concluded that; (a) The implementation of this activity has been able to improve literacy performance through training activities for novice researchers; (b) Give appreciation and attention to students by carrying out scientific activities at school and competing in the Olimpiade Sains Nasional; (c) Can anticipate the emergence of students' learning laziness and reluctance to be scientifically competent; (d) Being able to provide added value in the field of knowledge and skills for students so that they can complete school assignments given by teachers.